The Concept of ‘Life & Death’and ‘Innocence & Maturity’ in Kate Chopin’ The Awakening: Formal Criticism - Yanti Rahayuningsih; Ika Destina Puspita; Rahmatul Khasanah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study employs the formalism theory. Furthermore, aligning with it, the used of qualitative method to embark the information inherently exists as linguistic. It bears relevance to the focus of this research, that being novels, with the researcher endeavoring to scrutinize the characters' perspectives, viewpoints, and conduct within their fictional environment. The novel, The Awakening is utter the journey of unique married woman, Mrs. Edna Pontellier, to unfold the secret of ‘Edna’. From the analysis indicated there were two major ironies which majorly decorated the progress of the story, and those are ‘life and death’ and ‘innocence and maturity’. By bringing ‘Edna’ the main character, into a consciousness, she would awaken from seemingly an innocent woman through challenging journey to acknowledge maturity in herself. Even though, ironically, in order to maintain her ’life’ in the end she has to face ‘death’ but at least she had been tried to complete her journey to be an whole self.